The impact of employee voice on creative performance: An analytical research in the number of industrial companies - Juda Badi , Wafaa; D. Al-Zubaidi, Ghani. (Journal of Economics and Administrative Sciences, 2024)
Today, business organizations , seek to build creative capabilities by adopting advanced management concepts and methods such as employee voice to enable them facing potential challenges. This research investigates the impact of employee's voice on creative performance in a number of industrial companies in Baghdad City. The research's problem is started by the issues with weakness in corporate consciousness and the knowledge of employee voice that restrict firms from developing and innovating, and ignoring those voices except concerning the interest of companies. The main question of the research's problem is (What is the level of impact for employee voice on creative performance?). For the importance of the industrial sector in Iraq, the three companies which are Baghdad Soft Drinks Company, Electronic Industries Company, and the Iraqi Company for Carton Industry have been selected as a research domain. The research sample consists of 168 employees who work at these companies. Regarding to the statistical aspect, this research used the confirmative analysis coefficient, Cronbach's alpha coefficient, the weighted arithmetic, the standard deviation, the mean, the coefficient of relative difference, and relative weight (relative importance). The questionnaire was used as a main instrument for collecting data. Hypotheses were tested through statistical programs (AMOS.V.25, SPSS.V).  One of the most important findings is the significant positive impact of employee voice on creative performance. Research type: Research paper